Considerations for Managing Greenhouse Pests - Florida Greenhouse Vegetable Production Handbook, Vol 3: HS924/CV248, rev. 2013 - Rich, J. R.; Webb, S. E.; Paret, M. L.; Momol, M. T. (EDIS, 2013)
This document is HS924, one of a series of the Horticultural Sciences Department, UF/IFAS Extension. Original publication date December 1990. Revised September 2013.